2015
DOI: 10.1515/hf-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Superior cellulose-protective effects of cosolvent during enhanced dissolution in imidazolium ionic liquid

Abstract: To improve the solubility of cellulose at lower temperatures, several polar organic solvents were examined as cosolvents in imidazolium ionic liquid (IL). All tested cosolvents increased the solubilization efficiency of ILs at lower temperatures. Among these, N-methylimidazole, N-methyl-2-pyrrolidone, and dimethyl sulfoxide (DMSO) were notably efficient; in case of Avicel the solubility was increased, with 12–15% cellulose dissolution in 1-allyl-3-methylimidazolium chloride ([Amim]Cl) at 30°C. IR spectra of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, without cosolvent, all of the AAILs failed to dissolve cellulose (Avicel), even at 120°C (Table 1, entries 1, 8, 15, and 17). Therefore, the above-mentioned aprotic polar organic solvents served as cosolvents because they increased the solubilization efficiency of 1-allyl-3-methylimidazolium chloride ([Amim]Cl) for cellulose dissolution (Tao et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, without cosolvent, all of the AAILs failed to dissolve cellulose (Avicel), even at 120°C (Table 1, entries 1, 8, 15, and 17). Therefore, the above-mentioned aprotic polar organic solvents served as cosolvents because they increased the solubilization efficiency of 1-allyl-3-methylimidazolium chloride ([Amim]Cl) for cellulose dissolution (Tao et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that no significant degradation occurred during the dissolution process. Tao et al (2016) showed that polar organic cosolvents not only increase cellulose solubility in [Amim]Cl but also exhibit protective effects preventing DP decrement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed the improved dissolving ability to the preferential solvation of the cations of the IL by the aprotic polar solvent, as is supported by the conductivity measurements. Tao et al found that DMSO could not only promote the dissolution of cellulose in ILs, but could also show a superior cellulose-protective effect [ 40 ]. The degree of polymerization (DP) of cellulose was unchanged after dissolution and regeneration from the solvent system [Emim]Ac/DMSO, while the obvious reduction of the DP of cellulose was observed in pure IL.…”
Section: Dissolution Of Lignocellulosic Biomass In Ils and Il-basementioning
confidence: 99%
“…However, the poor solubility of cellulose in common solvents is the main obstacle to its further application. Ionic liquids (ILs) with negligible vapor pressure, strong solubilization efficiency, adjustable structure, and recyclability have been widely applied to lignocelluloses (Swatloski et al 2002;Zhang et al 2005;Fukaya et al 2006;Qu et al 2011Qu et al , 2012Qu et al , 2013aTao et al 2016a). After pretreatments with ILs, the highly crystalline structure of cellulose is altered to a disordered state with a more accessible surface area (Auxenfans et al 2012;Xiao et al 2012), which provides the possibility of transforming cellulose into advanced derivatives.…”
Section: Introductionmentioning
confidence: 99%